School Community Empowerment Program for Conservation of Riparian Vegetation around the Bedog River in Godean, Sleman - Abdul Razaq Chasani; Siti Aisah; Hayinnatus Sholihah; Handasari Mokodompit (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2023)
Due to the increasingly intensive interaction between humans and the river, the riparian vegetation conservation program was implemented to keep the Bedog River sustainable. This program aims to provide awareness and a good understanding of the dynamic balance between human life and the river environment, especially the conservation of riparian vegetation as a river key system that can be done. To achieve these aims, three approaches were implemented, i.e.: 1) empowering SMPIT Alam Nurul Islam Yogyakarta as a pioneer of the school community concern in the conservation of riparian vegetation by forming a "riparian class" equipped with learning modules for practising plant identification and research on vegetation profile analysis, 2) disseminating the conservation of riparian vegetation concept through the introduction of river bio-monitoring method for students and group activities by cleaning out the trash while doing outbound in the Bedog River, and 3) the involvement of all parties in the conservation of riparian vegetation by holding several focus group discussions with teachers and communities around the Bedog River. As an outcome, ESD-based learning on the conservation of riparian vegetation is included in the Biology Subject at SMPIT Alam Nurul Islam Yogyakarta, particularly in practical work. Then, every time a school outbound activity is held on the Bedog River, it is always accompanied by a trash clean-up activity. Also, there are efforts to use the communal land next to the school as an educational forest along with riparian vegetation conservation land.